Diseño e implementación de una solución de telecomunicaciones en ambiente de laboratorio que integre el estándar VDSL2 Vectoring bajo una arquitectura de acceso FTTC - Escobar Castillo, Evelyn Margoth (2017)
This project aims to verify operation of the vectorization technique applied to VDSL2. For this objective was implemented a research environment in a laboratory that consisting of a fiber (FTTC) and copper (VDSL2) network. Through this laboratory subscriber, loops with different length were simulated in order to observe bandwidth, SNR and attenuation behavior. Such experimentation was performed with ITU-T G.992.5, ITU-T G993.2 and ITU-T G993.5 standards, with a test protocol using TR-249 model and its respective analysis. Results show that maximum performance of the vectorization technique is obtained in a subscriber loop of up to 500 meters reaching bandwidths above 100 [Mbps], in addition the signal-to-noise ratio (SNR) improves by a factor of 19 % and we have a less attenuated channel by 16% with respect to VDSL2 when all lines that come from a DSLAM are vectorized.